Cross-Species Virus Transmission and the Emergence of New Epidemic Diseases - Parrish, Colin R.; Holmes, Edward C.; Morens, David M.; Park, Eun-Chung; Burke, Donald S.; Calisher, Charles H.; Laughlin, Catherine A.; Saif, Linda J.; Daszak, Peter (Microbiology and Molecular Biology Reviews, 2008)
Article Usage Stats Services MMBR Citing Articles Google Scholar PubMed Related Content Social Bookmarking CiteULike Delicious Digg Facebook Google+ Mendeley Reddit StumbleUpon Twitter current issue MMBR About MMBR Subscribers Authors Reviewers Advertisers Inquiries from the Press Permissions & Commercial Reprints ASM Journals Public Access Policy MMBR RSS Feeds 1752 N Street N.W. • Washington DC 20036 202.737.3600 • 202.942.9355 fax • journals@asmusa.org Print ISSN: 1092-2172 Online ISSN: 1098-5557 Copyright © 2014 by the American Society for Microbiology. For an alternate route to MMBR .asm.org, visit: MMBR